Pemroduksian Media Pembelajaran dan Instrumen Soal Berbasis Gamification bagi Guru-Guru di Kecamatan Nekamese - Heru Christianto; Yosep Lawa; Lolita A.M. Parera; Sudirman Sudirman; Dorthea M.W. Nay; Ni Wayan O.A.C. Dewi; Eka C. G. Kerihi (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2024)
The dedication to this community is the training of teacher competence development related to learning media that is carried out for teachers in the Nekamese, Kupang District, East Nusa Tenggara Province in the year 2023. The implementation is based on the need for teachers to develop competence against the use of technology in making learning media in accordance with the requirements of the independent curriculum in force today. This activity aims to enhance the competence of teachers in the use of technology in order to design interesting and innovative learning. In today's digital age, teachers are not only required to improve their teaching skills based on their material knowledge, but are also required to be able to apply innovative and enjoyable learning to encourage and motivate students in learning and thinking at a high level. The learning media used in this activity is the creation of teaching materials using exe learning, live worksheet and instrumentation using blookets. There are still many teachers in the Nekamese district who have never developed innovative teaching materials with the use of technology. Usually the teachers only teach in front of the methods of lectures and group discussions, and still give the questions of practice or examination in the form of manuals. As a result, students are less motivated and tired of learning. Therefore, through this training, teachers are trained and guided in creating gamification-based material and instruments until the product is produced and applied in classroom learning. This learning media can be presented in an interactive and interesting way so that it will motivate students to follow the learning. Teachers will also be increasingly creative in innovating to develop teaching materials and instruments of interest to students.